The Dynamics of Communal Participatory Communication in the Anticipation of COVID-19 Pandemic on WhatsApp Group Media - Dwi Kartikawati (Universitas Multimedia Nusantara, 2021)
Abstract This research has been conducted on the dynamics of communal participatory communication on WhatsApp group among residents within a particular neighborhood in Pasar Minggu, Jakarta, in their effort to anticipate COVID-19 pandemic. It ascertains that the effort against the pandemic is not only the responsibility of the government, but also of every individual in the country. Therefore, the role of the neighborhood committee is very crucial, as a government agent, in this endeavor to fight the pandemic. This participatory communication allows for people to create a space to exchange information and knowledge. In regard to this venture, WhatsApp provides virtual public spaces essential to accommodate and establish participatory communication through its Group Chats. The theoretical frameworks used in this qualitative research were participatory communication, the concept of dynamics, WhatsApp as a communication medium and virtual public sphere. The data used in this research were gathered from observing several case studies. The result demonstrated that the participatory communication model conducted through a WhatsApp Group Chat among the residents was established based on 4 (four) components: i.e. heteroglossia linguistics, dialogic elements, polyphony and carnivalesque. The result of this research displayed a co-management communication model conducted by the residents via a virtual public chat room provided by WhatsApp in their attempts to address the COVID-19 pandemic. The dynamics of this communication model established a mechanism that allows for the residents to prevent further proliferation of the virus. From here, protocols were created and to be complied in order to ensure public safety and suppress the spread of this virus. After all, COVID-19 pandemic is not only about the danger of the virus itself, but also the extended effects towards the national economic resilience. Keywords: Parcipatory Communication, Social Media, WhatsApp